The Effect of Taro Starch (Colocasia esculenta L Schoott) Edible Coating on the Quality of Red Chili (Capsicum annuum L) - Nining Purwati; Ervina Titi Jayanti; Wiwik Ariska (Jurnal Penelitian Pendidikan IPA, 2024)
Edible coating is a barrier, thin layer of consumable material to maintain moisture and slow down the respiration process of a product. In order to preserve the quality of red chili, this study aims to find the ideal taro starch concentration to use as an edible covering. Six treatments of taro starch concentration—0, 1, 2, 3, 4, and 5%—were used in experimental research utilizing a completely randomized design (CRD). Hedonic organoleptic testing produced the data. Analysis of variance (ANOVA) is then performed based on the level of panelist preference, and an LSD test is applied if there is a significant difference. The findings indicated that a 5% concentration of taro starch works best as an edible covering material to preserve the quality of red chili